Panic Buying as a Cause of Inflation According to al-Maqrizi's Perspective - Dahliana, Difi (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2022)
The research was motivated by the phenomenon of panic buying that hit the whole world at the start of the COVID-19 pandemic, but studies on panic buying in Islamic economic discourse are still very limited, and no one has linked it to the theory of inflation from an Islamic perspective. Therefore, this study aims to classify panic buying as the cause of inflation from al-Maqrizi's perspective. This research uses qualitative methods with a literature study. The results showed that panic buying can be classified as